Surgical treatment of massive bleeding of a right aberrant subclavian artery after oesophageal stent removal - Michael Raum; Dietrich von Schweinitz; Jochen Hubertus (Journal of Pediatric Surgery Case Reports, 2018)
We report a case of a 9-year-old female who required surgical treatment and resuscitation after severe transoesophageal bleeding of a right aberrant subclavian artery (RASA). Bleeding of this RASA was caused by a mechanical irritation due to an oesophageal stent. The stent was placed weeks before to dilate the oesophagus after accidental ingestion of a caustic agent. Although conservative management of benign oesophageal stenosis in children is highly recommended, there are still some major complications to be considered. To avoid erosion of aberrant subclavian artery vascular rings and slings, as described in several case reports, these vessels should be excluded by computed tomography (CT) or magnetic resonance imaging (MRI) scans before placement of oesophageal stents. This case suggests that management of caustic ingestion in children is still a major challenge in paediatric surgical departments. Keywords: Paediatric surgery, Chemical Burn, Oesophageal stenosis, Oesophageal stenting, Vascular abnormalities, Right aberrant subclavian artery